Pemanfaatan Smartphone Dalam Perkuliahan Kalkulus II: Bagaimana Persepsi Mahasiswa? - Mitra Permata Ayu; Sonia Santani; Erenstina E. Bana Lado; Fransiska Mere (Universitas Muhammadiyah Sorong, 2023)
The aim of the research is to determine students' perceptions of using smartphones in Calculus II courses and provide knowledge about the importance of smartphones in Calculus II courses as a tool to strengthen student understanding and improve learning outcomes. The subjects in this research were 16 third semester students majoring in Informatics Engineering in regular and extension classes who had taken the Calculus II course in the even semester, selected randomly. The data collection method used was semi-structured interviews. then interviewed using semi-structured interviews. The results of the research were that 16 subjects interviewed agreed that smartphones were very helpful for students during the Calculus II lecture process in: 1) looking for additional material and example questions, 2) Makes it easier to complete college assignments, 3) Facilitates communication with friends and lecturers, 4) Utilize learning applications such as symbolab, geogebra, online calculator, brinly. The obstacles experienced by students in using smartphones in Calculus II courses are: 1) Expensive internet packages; 2) Difficult network access; 3) Mobile phone memory storage is small.